Assessing the accuracy of self-reported self-talk - Brinthaupt, Thomas M.; Benson, Scott A.; Kang, Minsoo; Moore, Zaver D. (Frontiers in Psychology, 2015)
Self-Talk Scale (STS; Brinthaupt, Hein, & Kramer, 2009) is a self-report measure of self-talk frequency that has been shown to possess acceptable reliability and validity. However, no research using the STS has examined the accuracy of respondents’ self-reports. In the present paper, we report a series of studies directly examining the measurement of self-talk frequency and functions using the STS. The studies examine ways to validate self-reported self-talk by (1) comparing STS responses from 6 weeks earlier to recent experiences that might precipitate self-talk, (2) using experience sampling methods to determine whether STS scores are related to recent reports of self-talk over a period of a week, and (3) comparing self-reported STS scores to those provided by a significant other who rated the target on the STS. Results showed that (1) overall self-talk scores, particularly self-critical and self-reinforcing self-talk, were significantly related to reports of context-specific self-talk; (2) high STS scorers reported talking to themselves significantly more often during recent events compared to low STS scorers, and, contrary to expectations, (3) friends reported less agreement than strangers in their self-other self-talk ratings. Implications of the results for the validity of the STS and for measuring self-talk are presented.